Pengaruh Lama Waktu Pengasapan Terhadap Kualitas Ikan Cakalang (Katsuwonus Pelamis) dan Ikan Tuna Tongkol (Euthinus Affinis) Berdasarkan Hasil Uji Organoleptik di Kota Ternate” - M. Iksan B. Aly; Ermin Ermin; Mirna Koroy (Peneliti.net, 2022)
Smoked skipjack (Katsuwonus pelamis) and Tuna Tongkol (Euthinus Affinis) are one of the traditional processed products which are classified as smoked fish. The principle of processing is to give a certain amount of smoke with a certain smoking time to fresh fish, then smoked, smoking back and forth the smoked fish again until a distinctive aroma and quality of smoked fish can be smelled. The purpose of this study was to determine the effect of smoking time on the quality of smoked fish. This research is an experimental research. In this study, the researchers described the results of the assessment of the treatment carried out in smoking tuna and skipjack by using a long duration of smoking. Fish smoking equipment that has different functions and is made using a tongs grill consisting of 6 treatments. Each treatment was seen from the length of smoking 1-5 hours. After that, an analysis of the assessment of the panelists consisting of 10 panelists was carried out. The assessment procedure uses an assessment sheet. The value consists of taste, aroma, color and texture. From the results of the assessment then analyzed using the percentage formula. The results of the percentage analysis showed that the administration of various smoking with different durations of time in six treatments and one control resulted in significantly different results. This is indicated by the panelists' scores from the percentage formula